Superstructure formation and faceting in the Cu(210)-O system studied by scanning tunneling microscopy - Wee, A; Foord, J; Egdell, R; Pethica, J (1998)
The interaction of O on Cu(210) has been investigated by scanning tunneling microscopy. Adsorption at room temperature followed by high-temperature annealing leads to a series of mesoscopic superstructures ordered on different length scales ranging between 15 and 150 Å. By contrast, adsorption at high temperatures leads to the formation of a (2 × 1) superstructure similar to that found on Cu(110).